As dimensões esquecidas pelo direito do trabalho: composições e reflexões a partir de Hannah Arendt - Matheus Campos Caldeira Brant (2012)
This dissertation investigates the dimensions of the work that the LaborLaw does not recognize as worthy to receive legal protection as, for instance, the satisfaction, the recognition, the achievement, the projection. In short, subjective dimensions of the worker in his work. In order to understand why the Labor Law is constituted in this manner, it was tried to find the opposite, in other words, what is the central object of Its legal protection, and It was identified that Its main concern is with the material maintenance of the workers. All Its norms, principles and institutions are meant to provide the worker nourishment by a financial reward. Once it was diagnosed, it was found in the work The HumanCondition, Hannah Arendt, a possible answer to this fact: the prevalence in our society of the activity "work" over the other human activities, and to solve this problem, Arendt suggests that it should be paid more attention "to the thoughts of the artist." Relying on this last observation, it was tried to compose songs that could interact with the studied themes, revealing subtleties that sometimes escapes the academic gaze.